Transitory Price Changes and Price-Limit Rules: Evidence from the Tokyo Stock Exchange - George, Thomas J.; Hwang, Chuan-Yang (Journal of Financial and Quantitative Analysis, 1995)
Thomas J. George, Chuan-Yang Hwang, Transitory Price Changes and Price-Limit Rules: Evidence from the Tokyo Stock Exchange, The Journal of Financial and Quantitative Analysis, Vol. 30, No. 2 (Jun., 1995), pp. 313-327